(untitled) (Bangladesh Journal of Anatomy, 2019)
Introduction: Plastination is a process intended to preserve the biological specimens in the field of educational and research purposes. The plastinates are natural looking, dry, odourless and highly durable. But during dealing with plastination in research, there are some other problems that may arise such as shrinkage, changes in flexibility and colour. So for getting good quality plastinates, it should be tried to minimise the shrinkage, changes in flexibility and colour. This research is designed to compare the effect of temperature on the changes in the flexibility of goat livers. Objective of this study is to compare the percentage of change in flexibility of goat liver in different stages of silicone (S10) plastination at cold temperature with those at room temperature. Methods: A total of twelve (12) goat livers were collected from two government authorised slaughter houses of Dhaka. The percentages of changes in flexibility were calculated for different stages of plastination at cold temperature and at room temperature. This experimental study was carried out in the department of Anatomy, Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh. Result: The overall mean (± SD) percentage change in flexibility was 95.90+1.74% at cold temperature group and it was 96.86+1.29% in room temperature group. Conclusion: The concept of plastination is new in Bangladesh. So to produce good quality plastinates, it is essential to find out some techniques that are feasible in Bangladesh. Bangladesh Journal of Anatomy January 2019, Vol. 17, No. 1, pp. 21-24